Early detection, care and control of hypertension and diabetes in South Africa: A community-based approach - Sanele Madela; Shamagonam James; Ronel Sewpaul; Siyathokoza Madela; Priscilla Reddy (African Journal of Primary Health Care & Family Medicine, 2020)
Background: Non-communicable diseases (NCDs) are a major public health concern with raised blood pressure and glucose emerging as leading causes of death and disability. Aim: This community-based demonstration project using community caregivers (CCGs) trained in screening for hypertension and diabetes aimed at improving early detection and linkage to care and management. Setting: The project was conducted in KwaZulu-Natal province. Methods: The CCGs were trained in NCD-related health education, promotion and screening for hypertension and diabetes using an accredited programme. The CCGs screened community members for hypertension and diabetes using three screening methods: door-to-door visits, community campaigns and workplaces. Results: Twenty-five CCGs received the accredited NCD training. A total of 10 832 community members were screened for hypertension and 6481 had their blood glucose measured. Of those screened, 29.7% and 4.4%, respectively, had raised blood pressure (≥ 140/90 mmHg) and blood glucose (≥ 11.0 mmol/L) who required referral to a primary healthcare facility. More than one in five (21.0%, n = 1448), of those with no previous hypertension diagnosis, were found to have raised blood pressure at screening, representing newly detected cases. Less than a third (28.5%) of patients referred to the facilities for raised blood pressure actually presented themselves for a facility assessment, of which 71.8% had their hypertension diagnosis confirmed and were advised to continue, adjust or initiate treatment. Similarly, 29.1% of patients referred to the facilities for raised blood glucose presented themselves at the facility, of which 71.4% received a confirmatory diabetes diagnosis. Conclusion: Community caregivers played an important role in early detection of raised blood pressure and raised blood glucose, and in referring patients to primary care.